2020
DOI: 10.1002/jlb.3hi0220-130
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: AMPK regulates metabolic reprogramming necessary for interferon production in human plasmacytoid dendritic cells

Abstract: Plasmacytoid dendritic cells (pDCs) play a crucial role in innate viral immunity as the most potent producers of type I interferons (IFN) in the human body. However, the metabolic regulation of IFN production in such vast quantity remains poorly understood. In this study, AMP-activated protein kinase (AMPK) is strongly implicated as a driver of metabolic reprogramming that the authors and others have observed in pDCs after activation via TLR7/9. Oxygen consumption and mitochondrial membrane potential (MMP) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
2
28
1
Order By: Relevance
“…Because tumor is a heterogeneous disease, and its heterogeneity in cells and structure gives it a complex metabolic pattern. In fact, tumor cells mainly use the glycolysis pathway to quickly provide ATP (adenosine triphosphate) for their own growth, and also provide biological macromolecules for cell replication through the pentose phosphate pathway (PPP) and serine metabolism pathway [2,7]. For instance, under hypoxic conditions, tumor cells usually produce pyruvate through the glycolysis pathway, which in turn produces lactic acid instead of entering mitochondria and converting to Acetyl-CoA to produce ATP [1].…”
Section: Overview Of Metabolism Of Tumor Cells and Immune Cells 1 Metabolism Of Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because tumor is a heterogeneous disease, and its heterogeneity in cells and structure gives it a complex metabolic pattern. In fact, tumor cells mainly use the glycolysis pathway to quickly provide ATP (adenosine triphosphate) for their own growth, and also provide biological macromolecules for cell replication through the pentose phosphate pathway (PPP) and serine metabolism pathway [2,7]. For instance, under hypoxic conditions, tumor cells usually produce pyruvate through the glycolysis pathway, which in turn produces lactic acid instead of entering mitochondria and converting to Acetyl-CoA to produce ATP [1].…”
Section: Overview Of Metabolism Of Tumor Cells and Immune Cells 1 Metabolism Of Tumor Cellsmentioning
confidence: 99%
“…In fact, various central metabolism pathways can be dysregulated in cancer cells [2]. More importantly, emerging evidence indicates that cancer cells are able to suppress anti-tumor immune response by competing for and depleting essential nutrients or otherwise reducing the metabolic fitness of tumor-infiltrating immune cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Another critical signaling pathway that was downregulated during the CCHFV infection was AMP-activated protein kinase (AMPK) signaling that has been known to support IFN-I production through metabolic reprogramming. 30 In recent years, it has been recognized that metabolic pathways play a role in mounting effective IFN-I response 31 and the mechanisms are still not well understood. We observed a marked inhibition of CCHFV infection induced ISGs like ISG15, IFIT1, MX1 and MX2 mRNA levels upon blocking glycolysis and glutaminolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic requirements for this process are just beginning to be uncovered. It has been established that pDCs require both Oxidative metabolism (OxPhos) as well as glycolysis to maintain their function [ 116 , 117 , 118 ]. Furthermore, mammalian target of rapamycin (mTOR), a central regulator of metabolism, is essential for pDC IFN-I production [ 119 ].…”
Section: Suppression Of Pdc Ifn-i Production After Viral Infectionsmentioning
confidence: 99%
“…While multiple studies agree that pDCs adjust their metabolism after stimulation the details of these changes are still being established, Bajwa et al show that at 24 h post stimulation with influenza, lactate terminal glycolysis is enhanced in pDCs while OxPhos is slightly suppressed [ 116 ]. In contrast Hurley et al show that 6 hr of influenza or HSV exposure drives a slight increase in oxygen consumption rate (OCR) indicating increased OxPhos [ 118 ]. It is likely that the choice of distinct time-points in these studies is responsible for the observed differences.…”
Section: Suppression Of Pdc Ifn-i Production After Viral Infectionsmentioning
confidence: 99%